Analisis Waktu Kerja Pengemudi Bus terhadap Undang- Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan - Achmad Fauzan; Mudiana Permata Sari; Langga Lagandhy (Jurnal Pengembangan Ketenagakerjaan, 2025)
The working hours of bus drivers are regulated by applicable laws and regulations as well as the collective labor agreement (PKB) of PT. X. However, in practice, discrepancies are often found, such as working hours exceeding the maximum limit, lack of adequate rest time, and high operational demands. This study aims to analyze the implementation of bus drivers’ working hours at PT. X and examine its compliance with the requirements stipulated in Law Number 13 of 2003 concerning Manpower. The research employs a qualitative approach using a case study method. Data collection techniques include interviews, field observations, and documentation studies of the Collective Labor Agreement (PKB). The findings indicate that, normatively, PT. X has regulated drivers’ working hours in accordance with the law, namely eight working hours per day. However, field observations reveal excessive working hours experienced by bus drivers due to operational conditions such as traffic congestion and tight operational schedules. Additionally, the mandatory one-hour rest period is not always fully realized due to time constraints and field conditions. Although the PKB provides detailed protection of drivers’ rights, its implementation still requires close supervision to prevent violations of labor rights. This study recommends a review of the scheduling system and stricter supervision of the implementation of working hours and rest periods for bus drivers.